Growth respone, production and quality of grass resulted from addition of arbuscular mycorrhizal fungi and humic acid on acid soil with high aluminium content - Panca Dewi Manu Hara Karti; Y. Setiadi (Jurnal Ilmu Ternak dan Veteriner, 2011)
Arbuscular mycorrhizal fungi (AMF) can help plant to uptake of low P availability in acid soils because of the ability of AMF to adapt from acid soil. Humic acid plays a role in adsorption metals such as Al. The purpose of this research was to study the effect of addition of AMF and humic acid to acid soils on growth, yield and quality of grass. A complete randomized design with factorial pattern was applied to two types of grasses, namely: Setaria splendida (Al-tolerance) and Chloris gayana (Al-sensitive). The first factor is the addition of AMF, which consists of two levels, namely: -AMF = without AMF. +AMF = with AMF. The second factor was the addition of humic acid which consists of four levels, namely: Ho = without humic acid, H60 = 60 ppm humic acid usage, H120 = 120 ppm humic acid usage and H180 = 180 ppm humic acid usage. Variables measured were dry matter production of shoot and roots, uptake of P and N, the production of phosphatase, root infection, the number of spores. AMF and humic acid augmentation on Setaria splendida did not affect on growth and production, but they improved the uptake of P and N total. AMF augmentation enhanced growth, yield and quality of the Chloris gayana. The use of 180 ppm of humic acid could improve the quality of Setaria splendida and Chloris gayana. Key Words: Arbuscular Mycorrhizal Fungi, Humic Acid, Acid Soil, Setaria splendida, Chloris gayana